Patterns and Trends of Antimicrobial Resistance in Staphylococcus aureus Isolated in a Private Laboratory in Paraguay from 2020 to 2024 - Barrios Leiva, Julio César; Samudio Acevedo, Margarita; Guillén Fretes, Rosa María; Fariña, Norma; Vega, Ana; Pereira Fariña, Alicia; Rodríguez Acosta, Fátima (Medicina Clínica y Social, 2025)
Introduction: Staphylococcus aureus, a pathogen of global concern, has the ability to develop antimicrobial resistance, a factor that demands continuous surveillance. Objective: The objective was to determine the patterns and trends of antimicrobial resistance of S. aureus isolated from purulent secretions of patients attended at a private laboratory in Paraguay between 2020 and 2024. Methodology: This was a descriptive, retrospective study that used data from the electronic database of a private laboratory for the statistical analysis of variables such as antimicrobial susceptibility of S. aureus, from purulent secretion culture requests between 2020 and 2024. Results: S. aureus was isolated in 28.6% (220/770). Of these, 56.8% (n=125) were resistant to methicillin. A total of 61.5% (n=88) of the isolates were from outpatients. A moderate correlation was observed between methicillin resistance and resistance to ciprofloxacin (R²=0.709) and erythromycin (R²=0.705). The isolates showed resistance to erythromycin (66%), ciprofloxacin (34%), clindamycin (32%), and gentamicin (19%), but were 100% susceptible to trimethoprim-sulfamethoxazole and vancomycin. Among the multidrug resistance patterns in methicillin-resistant S. aureus, co-resistance to erythromycin-ciprofloxacin (37.5%) stood out. Conclusion: The increasing resistance to erythromycin, ciprofloxacin, and clindamycin limits their use in empirical treatments and highlights the importance of improving epidemiological surveillance strategies
Keywords: Staphylococcus aureus; Methicillin resistance; Multidrug Resistance